2011
DOI: 10.1007/s13324-011-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of spectral pairs

Abstract: In this paper we develop a geometric framework for spectral pairs and for orthogonal families of complex exponentials in L 2 (μ), where μ is a given Borel probability measure supported in R d .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…(5) We briefly talk about the connection of the extension problem with the Fuglede conjecture. (6) We state the relation of the extension problem for positive definite functions with the extension problem for stationary Gaussian stochastic processes. (7) We outline the extension of our main result (theorem 1.6) to the class of conditionally negative definite functions, which has applications to harmonic analysis of Gaussian stochastic processes, whose increments in mean-square are stationary.…”
Section: 2mentioning
confidence: 99%
See 1 more Smart Citation
“…(5) We briefly talk about the connection of the extension problem with the Fuglede conjecture. (6) We state the relation of the extension problem for positive definite functions with the extension problem for stationary Gaussian stochastic processes. (7) We outline the extension of our main result (theorem 1.6) to the class of conditionally negative definite functions, which has applications to harmonic analysis of Gaussian stochastic processes, whose increments in mean-square are stationary.…”
Section: 2mentioning
confidence: 99%
“…For background references on positive definite functions and their applications, see [5], [10], [25], [8], [6], [29], [28], [31]. In a special case, in [10], the idea of connecting spectral theory with the study of commuting selfadjoint extensions was suggested there.…”
Section: Introductionmentioning
confidence: 99%
“…Our analysis of Gaussian processes associated to covariance kernels with singular measure σ is motivated in turn by a renewed interest in a harmonic analysis of Fourier decompositions in L 2 (σ) for the case when σ is singular and arises from a scale of selfsimilarities; see for example [21,10,14,23]. In order to obtain a more versatile harmonic analysis in the study factorizations, one is naturally led to consideration of independence, but for a host of problems [13,22], rather than the traditional notion of independence, one needs a related but different notion, that of free independence.…”
Section: Introductionmentioning
confidence: 99%